2008
DOI: 10.1111/j.1467-8292.2008.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Différence De Satisfaction Dans l'EMPLOI Entre Secteurs À but Lucratif Et À but Non Lucratif: Le Rôle Joué Par Les Caractéristiques d'EMPLOI

Abstract: RÉSUMÉ**:  Cet article cherche à estimer, pour un échantillon issu de sept pays européens, le différentiel de satisfaction dans l'emploi entre les secteurs à but non lucratif et à but lucratif, et à en examiner les causes. La richesse des données utilisées permet, contrairement aux études antérieures, de prendre en compte les différences de caractéristiques d'emploi entre les deux secteurs. Les résultats obtenus révèlent que la plus grande satisfaction dans l'emploi des salariés du secteur à but non lucratif r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
1
15
0
3
Order By: Relevance
“…We also found that some practices present in FPOs, such as pay‐to‐performance linkage, are not included in the management style scale in NPOs, and therefore have no effect on employee job satisfaction in NPOs. These findings are consistent with previous studies (Lanfranchi and Narcy ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We also found that some practices present in FPOs, such as pay‐to‐performance linkage, are not included in the management style scale in NPOs, and therefore have no effect on employee job satisfaction in NPOs. These findings are consistent with previous studies (Lanfranchi and Narcy ).…”
Section: Discussionsupporting
confidence: 94%
“…Lanfranchi and Narcy () provided more detailed results using a dataset of EU NPOs in the service sector. They found that job satisfaction of NPO employees was mainly due to job characteristics, such as higher autonomy and intrinsic interest of the job.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For the central and local governments, grants can be politically attractive since employees and volunteers of nonprofit organizations delivering human services are also electors. In addition, the costs of services delivered through nonprofit organizations are generally lower than those directly provided by the state (Lanfranchi and Narcy 2008). Engaging nonprofit organizations is also a way to avoid expanding public employment, which is already very high in France.…”
Section: The Recent Shift From Grants To Contracts In a Context Of Nementioning
confidence: 99%
“…De même, l'engagement des bénévoles soulève la question de leurs motivations intrinsèques (Prouteau et Wolff, 2004) alors que, pour les employés, on s'interroge plutôt sur le niveau de leur rémunération, apparemment dans une position intermédiaire entre le secteur public et le secteur privé (Almond et Kendall, 2001), sans oublier les compensations non monétaires (Moscal et al, 2007). D'autres montrent que les caractéristiques de l'emploi doivent être prises en considération pour expliquer la différence de satisfaction dans l'emploi entre le secteur à but lucratif et le secteur à but non lucratif (Lanfranchi et Narcy, 2008). Par ailleurs, les articles portant sur les associations dans une perspective d'économie sociale soulèvent la question d'un financement approprié à partir de la finance solidaire et de la microfinance (Taupin et Glemain, 2007 ;Ferraton et Vallat, 2004 ;de Combrugghe et al, 2008).…”
Section: Montée Des Nouvelles Coopératives Et Des Associations (1986-unclassified